(3GdeHGOF hGdCUhd ddEOGQI hGdCYeGds - (3aQjO agej(B, (3RjGOIs ((3YeGf(B:s (3eWHYI GdTYH(B,s, 2006)
(3GdGOGQI(B: (3GdGOGQI hGdeOjQ, GdacQ GdJbdjOj, GdacQ GdGfSGfj, GdacQ GdMOjK hGdeYGUQ, GJNGP GdbQGQ, GdJNWjW, GdJfXje, GdGJUGd, GdbjGOI, GdQbGHI, GdeSDhdjI GdGLJeGYjI, GdCYeGd(B: (3GTcGd edcjI GdGYeGd, GOGQI GdYedjGJ, GOGQI GdJShjb, GdGOGQI GdeGdjI, GOGQI GdehGQO GdHTQjIs
Keywords: (3GOGQI GdGYeGds; (3GdGJUGds; (3GdJNWjWs; (3GdJfXjes; (3GdQbGHIs